Evaluation of marine sediment contamination by polycyclic aromatic hydrocarbons along the Karachi coast, Pakistan, 11 years after the Tasman Spirit oil spill. (October 2019) - Kahkashan, Sanober; Wang, Xinhong; Ya, Miaolei; Chen, Jianfang; Wu, Yuling; Cai, Yizhi; Saleem, Monawwar; Inam, Asif; Aftab, Javed
Abstract: On July 27, 2003, a spill of approximately 31, 000 tons of Iranian light crude oil affected the coast of Karachi, Pakistan. Approximately 11 years after the spill, we analyzed polycyclic aromatic hydrocarbons (PAHs) and their alkylated homologues (alkyl-PAHs) as the indicators to evaluate the residual effect of oil spill to the sediment along the Karachi coast. The total concentrations (dry weight) of parent PAHs and alkyl-PAHs ranged from 121.9 to 735.4 and 42.3–1149.9 ng/g, respectively. The estuary and harbor were the two regions with the highest levels of PAHs in the sediment. Conversely, sedimentary PAHs in the oil spill areas and remote coastal areas showed significantly lower levels. Although the results of the source identification indicated the up to 75.2% of the contribution from petroleum and its derivatives, this could only reflect the direct impact of the Karachi city on the presence of PAHs in the coastal sedimentary environment and did not indicated that the oil spill continues to stay 11 years later. Compared with 11 years ago, the sharply reduced PAH content, great changed composition, and the degradation driven trend of diagnostic ratios all indicated a sharp decrease in the influence of PAHs caused by the oil spill. Finally, the ecological risk caused by the PAH residual in the marine sedimentary ecosystem had disappeared along the Karachi coasts, Pakistan. Highlights: The concentrations of ∑16 PAHs in sediment was decreased 11 years after oil spill. ΣP-PAHs and ∑alkyl-PAHs provided better information to evaluate oil spill. PCA-MLR was employed to identify the petroleum-related sources of PAHs in sediment. PAHs would be unlikely to cause adverse effects.